An EPDM/MVQ polymer blend based magnetorheological elastomer with good thermostability and mechanical performance. Issue 42 (22nd October 2018) - Qi, Song; Yu, Miao; Fu, Jie; Zhu, Mi; Xie, Yuanpeng; Li, Wang
Abstract : We prepared an EPDM/MVQ blend based MRE with good thermostability and mechanical performance by using interface modification and polymer blending methods. Abstract : Magnetorheological elastomers (MREs) with outstanding magnetic-control properties are highly desirable for applications such as vibration attenuation, smart sensing, and soft robots. However, the low strength and thermolability of these materials still restrict their application in attenuating the vibration of large-scale devices. In this paper, we prepared an MRE based on ethylene-propylene-diene monomer (EPDM)/methylvinyl silicone rubber (MVQ) polymer blends. The resulting MRE showed good thermostability and mechanical properties. Good interfacial interaction and particle dispersion were achieved by modifying the surface of carbonyl iron powder (CIP) with silica coating by the sol–gel method. The compatibility between the EPDM and MVQ was promoted using silane coupling agents. Moreover, the resulting MRE had high mechanical strength and elongation at break. The dynamic viscoelastic properties of the MRE were tested using a rheometer. The influences of frequency, strain, matrices, temperature, and magnetic fields were discussed comprehensively, and relevant physical mechanisms were proposed. Finally, thermal aging tests were performed to evaluate the heat resistance of the MRE. Analytical results showed that the resulting MRE could be significantly applied to reduce the vibration of large devices because of its excellent mechanical properties and thermostability.